Mass scale seed production of indigenous small fish species: A promising solution to scale nutrition-sensitive aquaculture - Dubey, Sourabh; Rajts, Francois; Gogoi, Kalpajit; Das, Rashmi; Panemangalore, Arun; Belton, Ben; Chadag, Vishnumurthy Mohan; Bhadury, Punyasloke (Springer, 2025)
This book chapter explores the potential of indigenous small fsh (ISF) species as a solution to address undernutrition and promote nutrition-sensitive aquaculture. ISF, characterized by their small size and remarkable reproductive capacity, offer a rich source of protein, micronutrients, and essential fatty acids. Despite their nutritional advantages, ISF populations are declining due to habitat degradation and limited commercial cultivation. The integration of ISF into polyculture systems, particularly with carp, has shown promise in enhancing nutritional outcomes and overall productivity. However, the lack of techniques for commercial mass production and distribution of ISF seed poses a signifcant barrier to widespread adoption. This chapter highlights the importance of developing scalable methods for ISF seed production and ongoing efforts in this regard. It explores the challenges and opportunities associated with induced breeding of ISF and discusses innovations in seed production to overcome barriers to scaling. Furthermore, it examines the benefts of stocking hatchery-reared ISF seed and the role of genomics in ISF breeding and conservation. The chapter concludes by emphasizing the need for collaboration among stakeholders and the involvement of governments to advance and disseminate nutrition-sensitive aquaculture practices, ultimately contributing to improved nutrition and food security.